American Artists in the American Ambassador's Residence in Paris - Plante, Michael; Rohatyn, Felix; Rosenblum, Robert (Paris : American Embassy Residence, 1998)
Innes, Georges ; Hassam, Childe ; Prendergast, Maurice ; Dove, Arthur ; Cornell, Joseph ; Hopper, Edward ; O'Keeffe, Georgia ; Lawrence, Jacob ; de Kooning, Willem ; Rothko, Mark ; Johns, Jasper ; Lichtenstein, Roy ; Kelly, Ellsworth ; Bourgeois, Louise ; Marden, Brice ; Sherman, Cindy
Engels
American Artists in the American Ambassador's Residence in Paris, The Art in Embassies Program, 1998
boek
Keywords: Amerika